Professionals' Perspectives on Supporting Deaf Multilingual Learners and Their Families. (26th August 2020) - Crowe, Kathryn; Guiberson, Mark
Abstract: Parents frequently report that advice from professionals is important in making decisions about how their child with hearing loss will communicate. Little is currently known about how professionals support parents raising children with hearing loss in spoken language multilingual environments, children who are described as d/Deaf multilingual learners (DMLs). The purpose of this phenomenological study was to gain insight into professionals' perspectives and experiences working with such families, particularly in relation to supporting parents in decision-making about multilingualism and language choice. Nineteen professionals discussed their experiences working with DMLs and their families, the role of professionals in decision-making about multilingualism and language choice, and the factors that they considered were important when supporting DMLs and their families. Inductive thematic analysis yielded three themes: child characteristics (language, development), negotiating and supporting language (information, parents' language, role of language, timing, leadership, language management), and professional issues (knowledge, resources). This paper provides an important insight into professional considerations in supporting DMLs and their families, such as the role and functioning of evidence-based practice.